Geographic, seasonal and ontogenetic variations of δ15N and δ13C of Japanese sardine explained by baseline variations and diverse fish movements - Sakamoto, Tatsuya; Kodama, Taketoshi; Horii, Sachiko; Takahashi, Kazutaka; Tawa, Atsushi; Tanaka, Yosuke; Ohshmio, Seiji (Progress in oceanography, 2023)
•Japanese sardine isotope ratios greatly vary geographically and seasonally.•Baseline fluctuation is the primary driver of sardine isotope composition.•Life-stage- and region-dependent fish movements also have significant impacts.•Mechanistic prediction of small pelagic fish isotopes is possible but challenging. Understanding and predicting variability in the stable isotope ratios of nitrogen and carbon (δ15N and δ13C, respectively) of small pelagic fish is crucial to enable isotopic studies of a variety of marine predators that feed on them. However, because the isotope ratios reflect plastic feeding habits and fish migration in addition to baseline variation, their predictions require a mechanistic understanding of how each factor contributes. Here, we investigated the habitat-wide variability of δ15N and δ13C of the Japanese sardine Sardinops melanostictus in the western North Pacific and its marginal seas (the East China Sea and the Sea of Japan). By combining this with the archived particulate organic matter (POM) dataset as a baseline, we aimed to understand how ecological processes and baseline fluctuations affect isotope ratios of the sardine. Both δ15N and δ13C of sardine showed significant geographical and seasonal trends, with higher values in southern nearshore areas, including the Seto Inland Sea, intermediate values in marginal seas and lower values in Pacific offshore areas. As the variations were largely consistent with the geographic trend and the temporally integrated seasonal trend of isotope ratios of POM, respectively, the baseline variations are the main determinant of sardine isotope composition. The trophic positions of sardine are therefore not significantly different between regions, with possible minor increases in the southern nearshore area. Adults showed less geographic variation than larvae and juveniles, likely due to slower turnover periods and wider migration ranges. Although larval and juvenile isotope ratios in marginal seas mostly reflected the local baseline, those in the Pacific offshore often reflected the baseline in the neighbouring southern region, suggesting contrasting juvenile movements between regions. Our results suggest that the δ15N and δ13C of Japanese sardine strongly reflect baseline variations, but can also be influenced by life-stage- and region-dependent fish movements, thereby demonstrating both the possibility and difficulty of mechanistically modelling the isoscapes of lower trophic position species.